Croatian white grape variety Maraština: First taste of its indigenous mycobiota. (December 2022) - Milanović, Vesna; Cardinali, Federica; Ferrocino, Ilario; Boban, Ana; Franciosa, Irene; Gajdoš Kljusurić, Jasenka; Mucalo, Ana; Osimani, Andrea; Aquilanti, Lucia; Garofalo, Cristiana; Budić-Leto, Irena
Graphical abstract: Highlights: This study represents the first report on indigenous mycobiota of Croatian white grape variety Maraština. Metataxonomic approach has enabled the identification of 25 different fungal genera. Aureobasidium was the dominant genus followed by Cladosporium and Metschnikowia . Regional and local scale differences in mycobiota composition were observed. Physicochemical characteristics of musts were influenced by geographical position. Abstract: The indigenous vineyard mycobiota contribute both to wine quality and vineyard sanitary status. Wines made from same grape variety but from different geographical locations are appreciated for their diversity. Because no information on indigenous mycobiota of Croatian grapevines is available, the aim of the present study was to start filling this knowledge gap by characterizing the indigenous mycobiota of Maraština variety. The use of metataxonomic approach has enabled the identification of 25 different fungal genera present on Maraština grape berries collected from 11 vineyards located within the Croatian coastal winegrowing region of Dalmatia (Northern Dalmatia, Dalmatian hinterland, Central and Southern Dalmatia). The substantial regional and local scale differences in their distribution were observed. Overall, Aureobasidium was the dominant genus followed by Cladosporium and Metschnikowia . Botrytis and Plenodomus were associated with the vineyards located in Central and Southern Dalmatia, whereas Pichia was associated with Northern Dalmatia vineyards. The largest abundance of Buckleyzyma, Cladosporium, Eremothecium, Fusarium, Papiliotrema, and Rhodotorula was observed in Dalmatian hinterland. Moreover, data suggested that climate conditions and soil type partially influenced the distribution of fungal communities. The local-scale differences emerged also for the physicochemical characteristics of fresh musts. The high malic acid content supported the development of Metschnikowia, and inhibited Fusarium growth, whereas a positive correlation between Erysiphe and pH values was observed. Sporobolomyces and Cystobasidium were negatively associated with high glucose concentration. The revealing of Maraština indigenous mycobiota provided information on the members of fungal community negatively influencing the grapevine sanitary status as well as those which could be employed in disease biocontrol.